Evaluación de la primera alimentación en larvas de capaz pimelodus grosskopfii bajo condiciones de laboratorio - Rubén Valbuena, V.; Zapata-Berruecos, Beatriz; Otero-Paternina, Angélica [UNESP] (My University, 2013)
Evaluate the performance and survival of capaz larvae Pimelodus grosskopfii after supplying live food (Cladocera, Copepod and Artemia Salina). Materials and methods. Capaz larva were placed in plastic containers with an useful volume of 3 L , and a larvae density of 10 L-1, they were fed four times a day during 15 days with newly hatched Artemia nauplii, Cladocerans of the genders Moina and Ceriodaphnia and Copepods calanoides. Capaz larva were weighed and measured at the beginning and the end of the experiment in order to evaluate their weight gain (WG), length gain (LG), specific growth rate (SGR), relative growth factor (RGF), and survival rate(S). Results. The treatment that showed the best results in WG, LG and S was the lot fed with Artemia nauplii (3.8±0.2 mg, 8±0.7 mm and 48.3% respectively), followed by sample supplied with Cladocera and Copepods. Conclusions. The Artemia nauplii treatment revealed the best results on the productive variables evaluated in P. grosskopfii larvae at the beginning of their exogenous feeding.
Evaluation of first feeding of capaz larvae Pimelodus grosskopfii under laboratory conditions
Keywords: Artemia; Cladocerans; Copepods; Pimelodus grosskopfii (Source: AIMS).